Personalised blood pressure management during major noncardiac surgery and postoperative neurocognitive disorders: a randomised trial - Julia Y. Nicklas; Alina Bergholz; Francesco Däke; Hanh H.D. Pham; Marie-Christin Rabe; Hanna Schlichting; Sophia Skrovanek; Moritz Flick; Karim Kouz; Marlene Fischer; Cynthia Olotu; Jakob R. Izbicki; et al. (BJA Open, 2024)
Background: It remains unknown whether there is a causal relationship between intraoperative hypotension and postoperative neurocognitive disorders. We tested the hypothesis that personalised—compared to routine—intraoperative blood pressure management reduces the incidence of postoperative neurocognitive disorders in patients having major noncardiac surgery. Methods: In this single-centre trial, 328 elective major noncardiac surgery patients were randomly allocated to receive personalised blood pressure management (i.e. maintaining intraoperative mean arterial pressure [MAP] above preoperative baseline MAP from automated 24-h blood pressure monitoring) or routine blood pressure management (i.e. maintaining MAP above 65 mm Hg). The primary outcome was the incidence of neurocognitive disorders (composite of delayed neurocognitive recovery and delirium) between postoperative days 3 and 7. Results: The primary outcome, neurocognitive disorders, occurred in 18 of 147 patients (12%) assigned to personalised and 21 of 148 patients (14%) assigned to routine blood pressure management (odds ratio [OR]=0.84, 95% confidence interval [CI]: 0.40–1.75, P=0.622). Delayed neurocognitive recovery occurred in 17 of 146 patients (12%) assigned to personalised and 17 of 145 patients (12%) assigned to routine blood pressure management (OR=0.99, 95% CI: 0.45–2.17, P=0.983). Delirium occurred in 2 of 157 patients (1%) assigned to personalised and 4 of 158 patients (3%) assigned to routine blood pressure management (OR=0.50, 95% CI: 0.04–3.53, P=0.684). Conclusions: Personalised intraoperative blood pressure management maintaining preoperative baseline MAP neither reduced the incidence of the composite primary outcome neurocognitive disorders between postoperative days 3 and 7 nor the incidences of the components of the composite primary outcome—delayed neurocognitive recovery and delirium—compared to routine blood pressure management in patients having major noncardiac surgery. Clinical trial registration: ClinicalTrials.gov (NCT03442907).